Produção, caracterização e purificação de celulase de bactérias do trato intestinal de Diatraea saccharalis - Barbosa , Kledson Lopes (2019)
The development of processes for the production of cellulases with high specific activity is a challenge for industrial biotechnology. Although the performance of commercial cellulases has improved significantly in the last decade, the same has not happened with cellulases produced in research laboratories, being the production of this type of enzyme still a high cost factor in the processes that require its use. Thus, the present study aimed to investigate the presence of cellulolytic bacteria isolated from the intestinal tract of Diatraea saccharalis larvae in order to determine their potential use in the hydrolysis of sugarcane bagasse. For this, cellulolytic bacteria were screened from the intestinal tract of Diatraea saccharalis larvae through specific culture media using sugarcane bagasse and carboxymethylcellulose (CMC) as sole carbon sources. In this scenario, sugarcane bagasse was used as the inducible biomass of cellulase by means of liquid fermentation. Through an experimental planning were determined the best conditions of cellulase production (inoculum concentration and pH). The physico-chemical-morphological characterization of the biomass was performed by means of chromatographic (HPLC) and spectroscopic analyzes (FTIR, XRD). Then electrophoretic techniques were used to measure the endoglucanase protein profile of cellulolytic bacterial isolates, electrophoretic purification techniques to determine molecular weight of proteins and molecular techniques (PCR and DNA sequencing) for bacterial genome identification. The results of chemical characterization showed that cellulose and hemicellulose decreased after pretreatment, suggesting carbohydrate loss and formation of other products such as furfural, HMF, acetic acid and formic acid. FTIR spectra revealed similarity between untreated and pretreated material spectra, qualitatively evidencing that pretreatment was efficient in extracting hemicellulose and lignin. Peaks in the XRD diffractograms confirmed the removal of lignin and hemicellulose from the pretreated biomass. However, for the crystallinity index there was no significant change (73.25 and 73.70% for untreated and pretreated biomass, respectively). Gram staining of cellulolytic bacterial isolates revealed the presence of one Gram-positive encapsulated bacillus and three Gram-negative bacteria. The degradation activity of CMC revealed higher extracellular cellulase activity for the isolates INTB2, INTB3 and INTB4. For extracellular endoglucanase activity, the 4 isolates reported similar patterns of endoglucanase excretion, however, the INTB4 isolate reported the lowest extracellular activity (3.0 cm). The results of cellulase production through the INTB3 isolate showed to be more stable compared to the other isolates INTB1, INTB2, INTB4. As for purification, the specific activity for the INTB3 extract was 30.13 U/mg for INTB4 19, 97, INTB2 11,15 and INTB1 5,53 U/mg, after precipitation with ammonium sulfate. Native PAGE presented to the four isolates 3 protein bands corresponding to ~ 89, 58 and 48 kDa. In SDS-PAGE the enzyme extracts investigated (crude and precipitated) reflect multiple proteins detected in the gel and show that the enzymes presented several bands (between 150 and 17 kDa). The zymogram-CMC analysis exhibited cellulolytic activity, suggesting that the enzymes were able to hydrolyze sodium carboxymethylcellulose and have at least two sizes, ~ 89 and 58 kDa. The method applied for the cellulase isolation of the INTB3 isolate presented a single peak of cellulolytic activity and through 12% SDS-PAGE, 3 protein bands were observed around 113, 76, 52 kDa. In the present study, of the microorganisms isolated for enzymatic production, INTB3 was identified as the main producer of cellulase, having the highest specific activity after partial purification (30.13 U/mg). A purificação da endoglucanase de INTB3 através da cromatografia 11 por exclusão de tamanho triplicou (96,25 UI/mL) a atividade específica celulolítica. Mais distante outros estudos tornam-se importantes para dar continuidade a estes experimentos para obter alto rendimento de produção, purificação e aplicação de celulase.